Adipokinetic hormone activities in insect body infected by entomopathogenic nematode - Ibrahim, Emad Ahmed Sayed (Jihočeská univerzita, 2018)
The role of adipokinetic hormone (AKH) in the firebug Pyrrhocoris apterus adults infected by the entomopathogenic nematode (EPN) Steinernema carpocapsae was examined in this study. It was found that co-application of EPN and AKH enhanced firebug mortality about 2.5 times within 24 h (from 20 to 51% in EPN vs. EPN + AKH treatments), and resulted in metabolism intensification, as carbon dioxide production in firebugs increased about 2.1 and 1.6 times compared to control- and EPN-treated insects, respectively. Accordingly, firebugs with reduced expression of AKH receptors showed a significantly lower mortality (by 1.6 to 2.9-folds), and lower general metabolism after EPN + AKH treatments. In addition, EPN application increased Akh gene expression in the corpora cardiaca (1.6 times), AKH level in the corpora cardiaca (1.3 times) and haemolymph (1.7 times), and lipid and carbohydrate amounts in the haemolymph. Thus, the outcomes of the present study demonstrate involvement of AKH into the antistress reaction elicited by the nematobacterial infection. The exact mechanism by which AKH acts is unknown, but results suggested that the increase of metabolism and nutrient amounts in haemolymph might play a role.
Adipokinetic hormone activities in insect body infected by entomopathogenic nematode
Keywords: Mortality; Akh gene expression; AKH receptor; Metabolism; RNAi; Pyrrhocoris apterus; Mortality; Akh gene expression; AKH receptor; Metabolism; RNAi; Pyrrhocoris apterus